The inclusive quality of the school and the teacher's skills: a survey tool - Gabriella Ferrara (Firenze University Press, 2016)
For many years, research in pedagogical and educational field is sensitizing teachers on school inclusion and inclusive skills of teacher. This reflection in order to be transformed into an inclusive and conscious education needs assessment and monitoring tools both of the community in which the teacher works, and of the skills possessed by the teachers themselves. This work documents the process of construction and validation of an original instrument that allows teachers to self-evaluate their inclusive actions and, at the same time, detect the inclusive quality of the school. In the perspective of a pedagogy that looks for inclusion, the study will show the route taken and the methodology that was used for the preparation of a questionnaire able to provide specific forms of measuring for the evaluation of inclusive quality of school on one hand, and the promotion of methods of reflection about the didactic action that lead to the planning of an inclusive education and inclusive educational environments on the other. La qualità inclusiva della scuola e le competenze dell'insegnante: uno strumento di rilevazione Da molti anni la ricerca in campo pedagogico e didattico sta sensibilizzando i docenti sui temi dell'inclusione scolastica e delle competenze inclusive dell'insegnante. Tale riflessione per potersi trasformare in un agire educativo inclusivo e consapevole necessita di strumenti di valutazione e monitoraggio sia della comunità in cui il docente opera, sia delle competenze possedute dai docenti stessi. Il presente lavoro documenta il processo di costruzione e di validazione di uno strumento originale che permette allo stesso tempo agli insegnanti di autovalutare il proprio agire inclusivo e di rilevare la qualità inclusiva della scuola. Lo studio mostrerà, nella prospettiva di una pedagogia che guarda all'inclusione, il percorso compiuto e la metodologia che è stata utilizzata per la redazione di un questionario in grado di offrire, da un lato, specifiche forme di misurazione per la valutazione della qualità inclusiva della scuola, dall'altro, la promozione di processi di riflessione sull'agire educativo che conducano alla pianificazione di una didattica inclusiva e di ambienti scolastici inclusivi.